The Kombucha sebagai Alternatif Kesehatan dalam Konteks Quantum Entanglement di Era Pandemi COVID-19 Konteks Farmasi - Prasetyawan, Fendy; Saristiana, Yuneka; Muslikh, Faisal Akhmal; Azis, Asrizal; Wulan, Ema Tri (Journal of Social and Community Service, 2022)
In the challenging era of the COVID-19 pandemic, it becomes crucial to explore innovative health alternatives. Through community engagement, we highlight the role of Kombucha Tea as an intriguing health option, particularly within the context of quantum entanglement. Kombucha, a fermented beverage deeply rooted in various cultures, offers a spectrum of health benefits. In 2021, we conducted a series of socialization activities to disseminate knowledge about Kombucha Tea and underscore the importance of the holistic relationship between individuals, their environment, and health. Through informative sessions, practical workshops, and training programs, our objective was to enhance public awareness regarding the potential of Kombucha Tea in improving overall well-being.